Pengembangan E-Majalah Bernuansa Al-Qur’an Pada Materi Sistem Tubuh Pada Pembelajaran Biologi Untuk MTsN Kelas VIII Semester 2 - Ummi Hanafiah; M Haviz; Rina Delfita; Aidhya Irhash Putra (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The purpose of this research is to develop an E-Majalah with Al-Qur'an nuances on the Body System Material in Biology Learning for Valid MTsN Class VIII MTsN Semester 2. The results of the validation analysis obtained by the Al-Qur'an Nuanced E-Majalah were measured from the average validity with the results of 83% in the very valid category. Based on the results of the research that has been carried out, it can be concluded that the E-Majalah Biology with Al-Qur'an nuances on the body system material developed is suitable for use in the learning process of Biology at MTsN/SMP class VIII on body system material (Excretion System, Movement System, Respiratory System, Circulatory System and Digestive System). This can be seen from the validation aspect with an average validity value of 83% with very valid criteria.